High incidence rate of human herpesvirus 6 infection after Bendamustine, Cytarabine, Etoposide and Melphalan conditioning regimen: A monocentric and retrospective study - Simon Favre; Mathieu Sauvezie; Stéphane Vigouroux; Reza Tabrizi; Marie-Sarah Dilhuydy; Gaelle Laboure; Margot Robles; Noel Milpied; Kamal Bouabdallah (Archives of Clinical Nephrology - Peertechz Publications, 2021)
Background: Following shortage of Carmustine, BeEAM regimen (Bendamustine, Etoposide, Cytarabine and Melphalan) was used before autologous transplant in relapsed/refractory lymphoma patients. We evaluated safety and efficacy of BeEAM compared to BEAM. Patients and methods: Ninety consecutive patients receiving BeEAM (30pts) (Bendamustine 100, 120 or 200 mg/m²/d) or BEAM (60 pts) were retrospectively analyzed.  Results: In the BEAM group, 68% had NHL and 32% HL compared to 87% and 13% in the BeEAM group (p = 0,014). Pts were in CR or PR at time of transplant. There was no difference regarding hematologic recovery and transfusion requirements. Highest dose of Bendamustine were associated with grade ≥ 2 kidney toxicity. We observed a significant higher incidence of symptomatic HHV-6 infection (53.3% versus 8.3%), digestive toxicity (36.6% versus 15%) and prolonged hospitalization (25 versus 21 days) with BeEAM. After a median follow up of 61 and 49 months for BEAM and BeEAM, 5y-OS and PFS (76% versus 67% and 56% versus 70%) and TRM (0% versus 3%) were not different. Conclusions: BeEAM with the highest doses of Bendamustine was associated with increased risk of HHV-6 infection, longer duration of hospitalization, higher rate of digestive toxicity and increased acute kidney failure while survival was comparable.